Modelling and Simulation of Central Controller to Control Power Sharing In Microgrid - Kaur, Amandeep (My University, 2014)
Presently most of the power generation is contributed by thermal power plants which are coal fired. Fossil fuels, such as coals, are limited in nature and we have to depend on renewable energy resources to sustain the growth of electrical power generation. Small microgrid with inter-connected renewable energy resources is emerging as an alternative means of support to the conventional power generation technique. In this research work, we have designed a model of microgrid using Simulink/Matlabsoftware. The microgrid central controller proposed in this work has several features for distribution of power among several loads as per available generation. In addition, whenever a fault occurs on main grid, it isolates the microgrid from the main grid for protection of microgrid. The central controller works in autonomous mode. Two types of central controllers are designed for the microgrid. One central controller can work based on amount of power demand of load and other can work based on desired level of voltage across the load. The central controller automatically disconnects the non-critical load whenever the capacity of microgrid is reduced in islanded mode.A sample study is also done using Simulink for the wind turbine based microgrid. Satisfactory results are obtained while the wind turbine based microgrid is simulated while feeding the critical and non-critical loads in grid connected and islanded mode. A sample model of microgrid with central controller is proposed based onthe electrical layout of Thapar University. The research work presented in this dissertation justifies that the microgrid central controller improves the reliability of the microgrid.
ME, EIED
Keywords: MGCC; DERs; PCC; UPQC; DG